MULTILINGUALISM POLICY IN INTERNATIONAL EDUCATIONAL PRACTICES - Mohinur Baxtiyorova Ixtiyorjon qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article examines the role of multilingualism policy in international educational practices. In the context of globalization, the use of multiple languages in education has become increasingly widespread. The study analyzes different approaches to multilingual education in various countries, highlighting both their benefits and challenges. The findings suggest that well-structured language policies enhance students’ cognitive abilities, intercultural competence, and global opportunities. However, limitations such as lack of qualified teachers, inadequate resources present significant challenges. The article concludes that a balanced and inclusive multilingual policy is essential for sustainable educational systems.